Social security, psychological threat, and corporate performance: An analysis of financial performance after enactment of a social security scheme in Nepal - Oli, Sudan Kumar; Dhakal, Sunita; Xie, Yuantao (Asian Development Policy Review, 2023)
The main objective of this study was to analyze the impact of the contribution-based social security scheme on corporate performance after the enactment of the new policy in 2018. Panel data from 2015 to 2021 with observations of 266 companies, including 38 corporations from the banking and non-banking sectors, was used to analyze the impact of the new policy on corporate performance. This impact, as well as the role of psychological fear, was examined using the difference-in-differences analysis method. The findings of the analysis revealed an adverse impact on corporate performance in the banking sector compared to the non-banking sector. The study also showed that the banking sector's psychological fear was greater than that of the non-banking sector after the implementation of the policy. The conclusions of this study are helpful in understanding the corporations’ performance gap before and after the policy, as well as in making a strategic plan to overcome the psychological fear of the employees. This study suggests that the social security fund should use a mass media orientation program to explain the benefits and scope of the new policy.